2013
DOI: 10.1558/jircd.v4i1.123
|View full text |Cite
|
Sign up to set email alerts
|

Turn-taking in Brazilian Sign Language

Abstract: This study investigates the interactional skills of fluent sign language users, with special attention to contexts of overlapping talk. Data from semi-spontaneous conversations were analyzed from the video record, transcribed in ELAN, with tiers for non-manual signals and with a ‘gesture phase’ analysis of manual signs. Results show that signers closely coordinate their contributions in accordance with the sequential implicativeness of gesture phases. They deploy conventional resources similar to those describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 24 publications
1
37
0
2
Order By: Relevance
“…Moreover, unlike previously argued by , there is now both qualitative McCleary and de Arantes Leite, 2013;) and quantitative evidence that sign language users orient to a one-at-a-time principle in taking turns. All in all, our study is consistent with the view that, despite the potential differences between the visual and acoustic language modalities, spoken and signed turn-taking may share more features than has previously been suggested.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Moreover, unlike previously argued by , there is now both qualitative McCleary and de Arantes Leite, 2013;) and quantitative evidence that sign language users orient to a one-at-a-time principle in taking turns. All in all, our study is consistent with the view that, despite the potential differences between the visual and acoustic language modalities, spoken and signed turn-taking may share more features than has previously been suggested.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, there are many other cases of overlapping movement of participants' articulators. As such it is important to consider, in the case of sign language, whether overlapping signs are in fact attended to as competitive turns by speech act participants McCleary and de Arantes Leite, 2013;). In the current study, we consider turns that make relevant a timely and contingent response on behalf of the addressee, namely question and answer sequences.…”
Section: Consequences For the Study Of Turn-takingmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, several studies further pinpointed the signers' orientation to precision-timing and orientation to the coordinated transition between signers on the basis of fine-grained analyses of participants' accomplishment of turn-taking (McCleary and Leite, 2013; Groeber and Pochon-Berger, 2014; De Vos et al, 2015). For example, in a recent conversation-analytic account, McCleary and Leite (2013) provide compelling evidence for several overlap resolution devices (Schegloff, 2000) that deaf participants rely upon for managing overlapping signing. These more recent studies have also demonstrated the importance of a clear definition of overlap with respect to the movement phases of signs (cf.…”
Section: Research On Turn-taking and Overlap In Sign Languagementioning
confidence: 99%